Methodological Fallacies in the Determination of Serum/Plasma Glutathione Limit Its Translational Potential in Chronic Obstructive Pulmonary Disease - Salvatore Sotgia; Alessandro G. Fois; Panagiotis Paliogiannis; Ciriaco Carru; Arduino A. Mangoni; Angelo Zinellu (Molecules, 2021)
This study aimed to review and critically appraise the current methodological issues undermining the suitability of the measurement of serum/plasma glutathione, both in the total and reduced form, as a measure of systemic oxidative stress in chronic obstructive pulmonary disease (COPD). Fourteen relevant articles published between 2001 and 2020, in 2003 subjects, 1111 COPD patients, and 892 controls, were reviewed. Nine studies, in 902 COPD patients and 660 controls, measured glutathione (GSH) in the reduced form (rGSH), while the remaining five, in 209 COPD patients and 232 controls, measured total GSH (tGSH). In the control group, tGSH ranged between 5.7 and 7.5 µmol/L, whilst in COPD patients, it ranged between 4.5 and 7.4 µmol/L. The mean tGSH was 6.6 ± 0.9 µmol/L in controls and 5.9 ± 1.4 µmol/L in patients. The concentrations of rGSH in the control group showed a wide range, between 0.47 and 415 µmol/L, and a mean value of 71.9 ± 143.1 µmol/L. Similarly, the concentrations of rGSH in COPD patients ranged between 0.49 and 279 µmol/L, with a mean value of 49.9 ± 95.9 µmol/L. Pooled tGSH concentrations were not significantly different between patients and controls (standard mean difference (SMD) = −1.92, 95% CI −1582 to 0.0219; p = 0.057). Depending on whether the mean concentrations of rGSH in controls were within the accepted normal range of 0.5–5.0 µmol/L, pooled rGSH concentrations showed either a significant (SMD = −3.8, 95% CI −2.266 to −0.709; p < 0.0001) or nonsignificant (SMD = −0.712, 95% CI −0.627 to 0.293; p = 0.48) difference. These results illustrate the existing and largely unaddressed methodological issues in the interpretation of the serum/plasma concentrations of tGSH and rGSH in COPD.